2014
DOI: 10.1371/journal.pone.0111489
|View full text |Cite
|
Sign up to set email alerts
|

Three Minutes of All-Out Intermittent Exercise per Week Increases Skeletal Muscle Oxidative Capacity and Improves Cardiometabolic Health

Abstract: We investigated whether a training protocol that involved 3 min of intense intermittent exercise per week — within a total training time commitment of 30 min including warm up and cool down — could increase skeletal muscle oxidative capacity and markers of health status. Overweight/obese but otherwise healthy men and women (n = 7 each; age  = 29±9 y; BMI  = 29.8±2.7 kg/m2) performed 18 training sessions over 6 wk on a cycle ergometer. Each session began with a 2 min warm-up at 50 W, followed by 3×20 s “all-out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
151
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 37 publications
15
151
1
3
Order By: Relevance
“…This means that a meta-analysis of the effects of the number of sprint 326 repetitions in a SIT protocol on insulin sensitivity and glycaemic control is also currently not 327 feasible. Nonetheless, the improvements in insulin sensitivity and glycaemic control observed 328 to date with SIT protocols incorporating two (50) or three sprints (22,23) are encouraging. 329…”
Section: Repetitions 314mentioning
confidence: 98%
See 2 more Smart Citations
“…This means that a meta-analysis of the effects of the number of sprint 326 repetitions in a SIT protocol on insulin sensitivity and glycaemic control is also currently not 327 feasible. Nonetheless, the improvements in insulin sensitivity and glycaemic control observed 328 to date with SIT protocols incorporating two (50) or three sprints (22,23) are encouraging. 329…”
Section: Repetitions 314mentioning
confidence: 98%
“…Whereas insufficient data for a meta-analysis is available for the effects of SIT on blood 320 pressure (14,23,76), blood lipid profile (4,76), and body composition (69,76), the effect of 321 SIT on insulin sensitivity and glycaemic control has received more attention (4,22,23,50,52, 322 60, 76). However, the methods used to assess the effects of SIT on these parameters have 323 varied, with different studies using oral glucose tolerance tests (4, 50, 52, 76), intravenous 324 glucose tolerance tests (22), euglycemic hyperinsulinemic clamps (60), or continuous glucose 325 monitoring (23).…”
Section: Repetitions 314mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SIT-induced improvements in aerobic and anaerobic parameters (i.e., V O 2max , time-trial performance, Wingate power) as well as cardiometabolic health (i.e., muscle oxidative capacity, insulin sensitivity) are not compromised with even shorter work bouts involving 10 s (Hazell et al 2010), 15 s (Zelt et al 2014), and 20 s Metcalfe et al 2012;Gillen et al 2014Gillen et al , 2016 of supramaximal exercise. When considering the metabolic demands of SIT (predominantly anaerobic), a traditional 30-s bout is characterized by rapid peak power generation during the initial seconds of exercise (<10 s) followed by a precipitous power decline over the remainder of the effort.…”
Section: Introductionmentioning
confidence: 98%
“…This excess postexercise oxygen consumption (EPOC) is a consequence of the greater metabolic perturbations created during intense exercise (Laforgia et al 2006) and has been shown to increase postexercise EE with both SIT (Hazell et al 2012;Chan and Burns 2013;Townsend et al 2014;Beaulieu et al 2015) and HIIT . Additionally, these protocols have been shown to acutely increase postexercise fat oxidation (Whyte et al 2010;Chan and Burns 2013;Beaulieu et al 2015) and chronically upregulate various enzymes and proteins involved in fat oxidation (Burgomaster et al 2008;Gillen et al 2013Gillen et al , 2014 and transport (Perry et al 2008). Thus, fat loss after SIT may be attributable to EPOC-driven elevations in resting EE combined with a substrate shift towards increased fat utilization, although there is some controversy regarding these effects (Williams et al 2013).…”
Section: Introductionmentioning
confidence: 99%